2016
DOI: 10.1111/mec.13484
|View full text |Cite
|
Sign up to set email alerts
|

The role of marine reserves in the replenishment of a locally impacted population of anemonefish on the Great Barrier Reef

Abstract: The development of parentage analysis to track the dispersal of juvenile offspring has given us unprecedented insight into the population dynamics of coral reef fishes. These tools now have the potential to inform fisheries management and species conservation, particularly for small fragmented populations under threat from exploitation and disturbance. In this study, we resolve patterns of larval dispersal for a population of the anemonefish Amphiprion melanopus in the Keppel Islands (southern Great Barrier Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Reefs inside marine reserves that contain stable and abundant populations of giant sea anemones, such as those examined in the present study, can potentially contribute to the replenishment of populations in surrounding areas ('spill-over effects'; Planes et al 2009), in that they benefit both the recruitment (Mumby et al 2007) and recovery of nearby populations (Mumby and Harborne 2010). Marine reserves also provide a source of anemonefish recruits to anemones outside the protected area (Planes et al 2009;Bonin et al 2016), which could contribute to mitigating declines in nearby anemone populations.…”
Section: Discussionmentioning
confidence: 87%
“…Reefs inside marine reserves that contain stable and abundant populations of giant sea anemones, such as those examined in the present study, can potentially contribute to the replenishment of populations in surrounding areas ('spill-over effects'; Planes et al 2009), in that they benefit both the recruitment (Mumby et al 2007) and recovery of nearby populations (Mumby and Harborne 2010). Marine reserves also provide a source of anemonefish recruits to anemones outside the protected area (Planes et al 2009;Bonin et al 2016), which could contribute to mitigating declines in nearby anemone populations.…”
Section: Discussionmentioning
confidence: 87%
“…Although reef fish larvae clearly have the potential for long-distance movements 14 , there is increasing evidence that dispersal may be more limited than previously assumed 15,16 . The most compelling evidence of larvae returning to natal or nearby reefs has come from chemical labelling of embryos 17,18 and genetic DNA parentage analyses [19][20][21][22][23][24][25][26][27] . However, few studies have been able to fully describe a dispersal kernel by determining the distances over which spatially fragmented subpopulations are connected by larval movements.…”
mentioning
confidence: 99%
“…This information can be incorporated into the design of MPAs and for defining management areas to help ensure continuous larval supply, enhancing the capacity of populations to recover from disturbances (Berumen et al, 2012 ; Hughes et al, 2010 ; Van Oppen & Gates, 2006 ) and improving the effectiveness of a broad range of conservation interventions (Christie et al, 2010 ; Magris et al, 2018 ). For instance, Bonin et al ( 2016 ) highlighted the resilience of anemonefish populations at the Keppel Islands (GBR) that are supplied and maintained by recruits from distant source populations even if local breeders are lost. Additionally, Hock et al ( 2017 ) showed that 112 reefs in the GBR have sufficient dispersal ability to facilitate recovery of disturbed areas, providing evidence for systemic resilience within the large reef system.…”
Section: Introductionmentioning
confidence: 99%